The influence of the independent non-executive board members on the financial performance of the companies listed in the Bucharest stock exchange - Bogdan Aurelian Mihail; Carmen Daniela Micu (Journal of Risk and Financial Management, 2021)
This paper studies the impact of independent board members on the financial performance of companies listed on the Bucharest Stock Exchange during the period 2016-2020. Different characteristics of the board of directors have been examined extensively in the literature and board independence was identified as one of the most effective corporate governance tools. In this context, the present study contributes to the relevant literature by examining recent data for Romania and investigating alternative performance indicators such as return on assets (ROA), return on equity (ROE) and Tobin's Q. The correlation analysis, scatter plots, and regression results document that a higher share of the independent board members was associated with higher returns on equity ratio. Specifically, a 10% rise in the share of independent members was associated with an approximately 0.9%-point increase in ROE.
Keywords: 330; board size; corporate governance; firm performance; independent board members; return on equity; Romania